Three essays on cross-border mergers and acquisitions - Chen, Yuhuilin (2017)
This thesis mainly focuses on three essays on cross-border M&As. A sample of Chinese outward mergers and acquisitions (M&As) between 1997 and 2011 involving Chinese listed firms as the acquirers is analysed in the first essay to highlight the relationship between political connections, financial constraints, and stock returns. On average, Chinese firms, especially private firms, are more likely to face financial constraints. However, the political connections can release these kinds of financial constraints. Less financially constrained firms have higher stock returns when there is an announcement of outward M&As.